Please wait...
1800-212-7858 (Toll Free)
9:00am - 8:00pm IST all days

or

Thanks, You will receive a call shortly.
Customer Support

You are very important to us

For any content/service related issues please contact on this toll free number

022-62211530

Mon to Sat - 11 AM to 8 PM

Pl. answer my question urgently

Asked by 10th March 2010, 10:18 AM
Answered by Expert
Answer:

ATQ,

when p(x) is divided by x-2, it leaves a rem of 1

so we get

p(x)=(x-2)q(x)+1...(i)

next it's given that when p(x) is divided by x-3 rem is 3

i.e.

p(3)=3

substituting in (i) we get

p(3)=[1 x q(3)]+1

but p(3)=3

so

3=q(3)+1

so

q(3)=2

i.e. when q(x) is divided by x-3 it leaves a rem of 2

i.e.

q(x)=[(x-3)r(x)]+2... where r(x) is (say) the quotient

so substituting this value of q(x) in (i) we get,

p(x)=[(x-2)q(x)]+1

=([(x-2){(x-3)r(x)+2})+1

=[(x-2)(x-3)r(x)]+[2(x-2)]+1

so

p(x)=(x-2)(x-3)[r(x)]+[2x-4+1]

so the  reqd rem is 2x-4+1=2x-3

Answered by Expert 10th March 2010, 4:35 PM
Rate this answer
  • 1
  • 2
  • 3
  • 4
  • 5
  • 6
  • 7
  • 8
  • 9
  • 10

You have rated this answer /10

Your answer has been posted successfully!

Chat with us on WhatsApp